2015
DOI: 10.1017/s0007114515001154
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns and their associations with childhood obesity in China

Abstract: Dietary patterns represent the combined effects of foods, and illustrate efficaciously the impact of diet on health outcomes. Some findings of previous studies have limited applicability to Chinese children due to cultural factors. The presnt study was designed to identify dietary patterns and determine their relationships with obesity among Chinese children and adolescents. Data collected from 1282 children and adolescents aged 7–17 years from the 2011 China Health and Nutrition Survey (CHNS) were used. Dieta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
90
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(103 citation statements)
references
References 42 publications
10
90
0
3
Order By: Relevance
“…This study also found that vitamin A was negatively associated with the traditional pattern due to the lower intake of animal-source foods. This result is consistent with previous studies that suggested a possible risk of micronutrient deficiency for people following a predominantly traditional dietary pattern [15,33]. The tuber pattern used to be common in rural China but has seldom been reported in recent years [39].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study also found that vitamin A was negatively associated with the traditional pattern due to the lower intake of animal-source foods. This result is consistent with previous studies that suggested a possible risk of micronutrient deficiency for people following a predominantly traditional dietary pattern [15,33]. The tuber pattern used to be common in rural China but has seldom been reported in recent years [39].…”
Section: Discussionsupporting
confidence: 93%
“…In this process, traditional dietary habits have changed resulting in an increased incidence of nutritional diseases. Recent studies in China have assessed dietary patterns and obesity among children and adults living in different parts of China, but the results were not consistent [14,15,16]. Although the shift in diet is nationwide, they are occurring at markedly different rates across the country due to economic disparity [17].…”
Section: Introductionmentioning
confidence: 99%
“…Han and Wen (2014) document a positive correlation between family income and childhood obesity by using the data from Shanghai. Zhang et al (2015) find correlation between northern dietary patterns and childhood overweight. As an emerging economy with deeprooted Eastern traditions, China exists within its own unique context.…”
Section: Introductionmentioning
confidence: 75%
“…The studies were all cross-sectional studies, with the exception of one case-control study. 70 The studies were conducted in nine different countries and the majority of studies were from Asian countries (Iran, 70 China, 61,65,66,69,71 and Lebanon 64,67 ), with four from American countries (Mexico, 58 Brazil, 60,63 and Colombia 62 ), two from European countries (Norway 57,59 ), one from Australia, 19 and one from Polynesia (Samoan island of Upolu 68 ).…”
Section: Study Characteristicsmentioning
confidence: 99%